A respeito do Processo de Kafka - Korfmann, Michael (Contingentia, 2009)
Based on a supposedly new discovery of pornographic magazines, James Hawes aimed, in Excavating Kafka (2008), to reset the almost saintlike image of Kafka. This article will argue that these publications are fare from being hard-core pornography and their existence has been a long known fact. It will then discuss relations between literary texts and biography with reference to Kafka’s novel Der Process, written in 1914 and published only posthumous.